PENGARUH ADVERSITY QUOTIENT TERHADAP TANGGUNG JAWAB BELAJAR MAHASISWA PGSD - Arifin, Nurdin (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
Sustainable development in the educational process is mandatory for the creation of conditions for individuals to act in complex situations in a sustainable manner. Adversity quotient gives individuals to deal with the difficulties they face, as well as the responsibility that students must feel for themselves so that it becomes important for the implementation of continuous learning. This study aims to reveal the effect of adversity quotient on the learning responsibilities of PGSD students at Widya Gama Mahakam University, which consists of 106 students. The research results show that there is an adversity quotient effect on student learning responsibility as indicated by the obtained t count, which is 5.260, which when compared to t table, which is 1.983, it is said that t count > t table.